ANALYSING THE BRONZE CASTING DEVELOPMENT OF CONTEMPORARY AND TRADITIONAL SCULPTURE IN TAMILNADU - Velayutham, Arun; K, Raman (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The art of sculpture in Tamil Nadu, India, pulsates with the rhythm of a vibrant history. For millennia, bronze casting has been a cornerstone of this artistic tradition, breathing life into deities, heroes, and narratives. However, contemporary expressions rise within this landscape, challenging and complementing the established forms. This article delves into this dynamic interplay, analysing the development of traditional and contemporary sculpture in Tamil Nadu, specifically focusing on the enduring and evolving art of bronze casting. The article aims to illuminate the state's rich tapestry of sculptural practices by examining case studies, exploring thematic concerns, and investigating socio-economic factors. Tamil Nadu boasts a vibrant tradition of sculpture, stretching back millennia and encompassing diverse materials, styles, and themes. This article delves into the fascinating dynamics between contemporary and traditional sculptural practices in the state. It examines how contemporary sculptors engage with, adapt, or challenge established forms, materials, and narratives, exploring the cross-pollination and tensions in this dynamic artistic landscape. The article analyses key trends and innovations within contemporary sculpture, highlighting the influence of globalisation, technological advancements, and social shifts. It also considers traditional sculptors' challenges in preserving their heritage while adapting to changing tastes and market forces. Through this comparative analysis, the article aims to shed light on the evolving nature of sculpture in Tamil Nadu and its potential future directions.